A scoping review on the influence of contextual factors on training load in adolescent soccer players: What do we know? - Nijland, R.; Toering, T.; Watson, C. G.; de Jong, J.; Lemmik, K. A. P. M. (Sports, 2024)
This scoping review aimed to systematically explore the breadth and extent of the literature regarding the relationship between contextual factors (CFs) and training load (TL) in adolescent soccer players. Further aims included comprehending potential underlying mechanisms and identifying knowledge gaps. CFs were defined as factors not part of the main training process, such as the coach-athlete relationship and educational responsibilities. PubMed, EBSCO APA PsycINFO, Web of Science, ProQuest Dissertations & Theses A&I, and SportRxiv were searched. Studies involving adolescent soccer players that investigated the CF-TL relationship and measured TL indicators were deemed eligible. Seventeen studies were included, reflecting the limited number of articles published regarding the CF-TL relationship. CFs were mostly related to match-play (N = 13) and phase of the season (N = 7). Moreover, these factors appeared to affect TL. CF related to players` personal environment (N = 3) were underrepresented in the reviewed studies. Overall, the CF-TL relationship appears to be rarely scrutinized. A likely cause for this lack of research is the segregation of the physiological and psychological research domains, where the CF-TL relationship is often speculated upon but not measured. Therefore, a holistic approach is warranted which also investigates the effect of personal environment, such as stressful life stress events, on TL.